An intergenerational playgroup in an Australian residential aged‐care setting: A qualitative case study. (27th August 2020) - Rosa Hernandez, Gabrielle B.; Murray, Carolyn M.; Stanley, Mandy
Abstract: Intergenerational programs are emerging within the aged‐care context as they provide a unique opportunity for older adults living with or without cognitive impairments to connect with children. One type of intergenerational program is an 'intergenerational playgroup' which creates opportunities for children to develop their skills, parents to create a local peer support network and provides older adults at risk of isolation with vital community interaction. The objective of this research was to evaluate an intergenerational playgroup taking place weekly within a residential aged‐care setting. A qualitative case study research design was used to perform five observation sessions and semi‐structured in‐depth interviews. All members of the group (older adults and caregivers) as well as involved staff were invited to participate. Consent from any older adults with known cognitive impairment was sought from next of kin. Consent for children was provided by caregivers. A total of 12 clients ( n  = 8 diagnosis of dementia, 4 without dementia; 11 females, 1 male), three staff members, and 10 caregivers and their children (0–5 years) provided consent to be observed. Of these, five older adults (all female, 1 with diagnosis of dementia), three staff and five caregivers participated in interviews. Data were analysed thematically. Four key themes : Learning from each other; Appreciating experience in the moment; Connecting through play; and A sense of home and belonging were identified. These themes suggest that older adults play an active role in the dynamics of the playgroup, often being 'in the moment' during play, but also actively reminiscing on their past experiences of childhood. The sense of an inclusive and supportive community with a culture of being open to learning and to different perspectives was strong. The findings support the role of intergenerational playgroups for promoting community engagement with benefits of building relationships and connectivity for all stakeholders.